T2DM patients’ demographic characteristics as moderators of the relationship between diabetes perception and psychological distress - Kugbey, N.; Atindanbila, S.; Nyarko, K.; Atefoe, E.A. (International Journal of Applied Psychology, 2015)
This study examined the relationship the relationship between T2DM illness Perception and Psychological Distress and further investigated whether this relationship is influenced by demographic characteristics such as Sex, Age and level of Education. A total of 139 persons living with T2DM were sampled from Korle-Bu Teaching Hospital in Accra, Ghana. The respondents were administered with demographic questionnaire, the Brief Illness Perception Questionnaire and the Brief Symptom Inventory. Pearson correlation and Hierarchical Multiple regression analyses were done and the results indicate that illness perception is significantly and positively associated with the level of psychological distress among persons with T2DM. However, this relationship was not significantly moderated by their sex, age and level of education. The findings from the study indicate that the association between illness perception and psychological distress among persons with type-2 diabetes is not significantly affected by their demographic characteristics age, sex and level of education. It is therefore concluded that the focus of psychological interventions should be targeted at modifying the negative thought patterns of the patients regarding their illness.
Keywords: Illness Perception; Psychological Distress; T2DM; Ghana